2014 13th Annual Mediterranean Ad Hoc Networking Workshop (MED-HOC-NET) 2014
DOI: 10.1109/medhocnet.2014.6849118
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dynamic frame Aloha with frame restart

Abstract: Abstract-This paper provides an analysis of the Dynamic frame Aloha (DFA) protocol with frame Restart. Although a previous work has numerically provided the best restarting strategy when the number of tags N is known, that strategy is represented by a table whose entries are so many to be impractical for high values of N . Here we provide a simpler set of equations that, besides the optimal strategy, lead to a very simple sub-optimal strategy whose performance is practically indistinguishable from the optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In this paper we generalize the approach already exposed in [18] and, after deriving the asymptotic efficiency of the Schoute's estimate, equal to 0.311, we use it to prove that estimate proposed in [13] is asymptotically efficient, namely is able to reach e −1 .…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In this paper we generalize the approach already exposed in [18] and, after deriving the asymptotic efficiency of the Schoute's estimate, equal to 0.311, we use it to prove that estimate proposed in [13] is asymptotically efficient, namely is able to reach e −1 .…”
Section: Introductionmentioning
confidence: 89%
“…The aim is at maximizing efficiency, defined as η(N ) = N/L(N ), being L(N ) the average number of slots needed to identify all N tags. In [12] we have proved that, when N is known, the optimal frame setting is r = n, and the asymptotic efficiency, as N → ∞, is e −1 , while in [13] we have shown that the FR procedure does not improve the DFA asymptotic efficiency. In practice N is often unknown, and it turns out that the efficiency suffers from the mismatch between N and the initial frame length r 0 , especially when N is unbounded, as it can be in future applications.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations